1964
DOI: 10.1152/ajplegacy.1964.206.5.1161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic hypothalamic lesions on diurnal and stress corticosteroid levels

Abstract: The effect of chronic lesions on plasma corticosteroid levels has been assessed in an attempt to differentiate neuronal areas affecting diurnal corticosteroid rise from those involved in acute response to stress. In unanesthetized, unrestrained rats blood samples were collected through a chronic indwelling catheter on each of four experimental days at 9 and 10 am and 5 pm with or without addition of a stress applied at 9:45 am. Anterior hypothalamic lesions bilaterally destroying the periventricular zone and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…The basis for this discrepancy is unknown. Although the neuroanatomy of the fornix is consistent with the possibility that its destruction is the common de nominator in the disruption of rhythm produced by anterior hypo thalamic cuts [ H a l a s z et a!., 1967; M o o r e and E ic h l e r , 1972] or electrolytic lesions [Slusher, 1964;Moore and Eichler, 1972], the persistence of normal diurnal excursions in corticosterone levels in the absence of the hippocampo-fornix system indicates that these struc tures arc not essential for this neuroendocrine rhythm. The retention of this rhythm, despite the imposition of the massive neural lesions used in these studies, suggests that only specific manipulations will result in the disruption of this aspect of pituitary-adrenal function.…”
Section: Discussionmentioning
confidence: 91%
“…The basis for this discrepancy is unknown. Although the neuroanatomy of the fornix is consistent with the possibility that its destruction is the common de nominator in the disruption of rhythm produced by anterior hypo thalamic cuts [ H a l a s z et a!., 1967; M o o r e and E ic h l e r , 1972] or electrolytic lesions [Slusher, 1964;Moore and Eichler, 1972], the persistence of normal diurnal excursions in corticosterone levels in the absence of the hippocampo-fornix system indicates that these struc tures arc not essential for this neuroendocrine rhythm. The retention of this rhythm, despite the imposition of the massive neural lesions used in these studies, suggests that only specific manipulations will result in the disruption of this aspect of pituitary-adrenal function.…”
Section: Discussionmentioning
confidence: 91%
“…The results in the 30-day-old animals treated neonatally with hydro cortisone also provide another example [Slusher, 1964; K r ie g e r et al, 1968; K r ie g e r and Rizzo, 1969] of an experimental situation in which it is possible to alter the circadian periodicity of plasma corticosteroid levels without interfering with other aspects of the CNS-pituitary-adrenal axis. Some qualification should be made in view of the finding that 30-day-old female and 80-day-old male animals treated neonatally with hydrocortisone had enhanced responsiveness to a given dose of ACTH.…”
Section: Discussionmentioning
confidence: 95%
“…This laboratory has previously reported that the circadian rise in plasma corticosteroid levels in 30-day-old rats is obliterated by the admin istration of either hydrocortisone or dexamethasone within the first 4 days of neonatal life, but not if given on day 12 of neonatal life [Krieger, 1972], There is also evidence that (a) the neural pathways [Slusher, 1964] and/or neurotransmitter agents [Krieger et al, 1968;Krieger and Rizzo, 1969] involved in the stress responsiveness of the central nervous system (CNS)-pituitary-adrenal axis are different from those concerned…”
mentioning
confidence: 99%
“…Their results indicate that the cerebral cortex as well as a number of subcortical structures, including the limbic system, are dispensable for the persistence of circadian rhythmicity. In this regard, the observations by Slusher (1964) are pertinent. She reported that lesions located in the anterior periventricular zone and the arcuate nucleus abolished the circadian rhythmicity of plasma corticosterone in the mouse, whereas electric destruction of the posterior tuber cinereum did not.…”
Section: Discussionmentioning
confidence: 96%